Smart escapes: travel big on a small budget - Abdul Karim, Yaasmin Farzana; Md Kamdari, Nor’azurah; Mohd Sharip, Sharfizie; Othman, Farrah (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2025)
After a busy school term or work period, many people look forward to a vacation as a way to relax and recharge. However, travel expenses such as flights, accommodation, food, and activities can quickly add up, making it seem unaffordable. The good news is that with careful planning, flexibility, and smart budgeting, it’s possible to enjoy a memorable trip without overspending or draining savings.